Work Environment, Motivation, and Tutor Performance: Job Satisfaction as Mediator in Language Course Institutions - M. Arifin; Dodi Wirawan Irawanto; Margono Margono (International Journal of Nusantara Islam, 2026)
This quantitative investigation examines the impact of workplace conditions and motivation on tutor performance, incorporating job satisfaction as a mediating factor. Data was gathered via questionnaires distributed to tutors across 10 Training and Course Institutions (LKP) in Kampung Inggris, Pare, Kediri, Indonesia. From a total population of 185 tutors, 165 completed surveys were returned and analyzed. Researchers employed a non-probability sampling strategy, specifically judgmental purposive sampling. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate statistically significant positive effects: both the work environment and work motivation directly enhance tutor performance and also have a positive influence on job satisfaction. Furthermore, job satisfaction itself exerts a significant positive effect on performance. Crucially, mediation analysis confirms that job satisfaction partially mediates the relationship between the work environment and work motivation, and both of these factors influence tutor performance. These findings offer valuable insights for institutional enhancement strategies.